Bioethanol production from renewable polymer lichenan using lichenase from an alkalothermophilic thermomonospora sp and thermotolerant yeast - Menon, Vishnu; Divate, Rupesh; Rao, Mala (Fuel Processing Technology, 2011)
Biomass feedstocks available decentrally will be more commodious for localized biorefinery approach than the exhaustive large scale and centralized plants driven by cost intensive technology. Lichen is present in a wide range of habitats in a distributed manner. A maximum hydrolysis of 73%-76% for lichenan from Cetraria islandica, Usnea barbata and Parmelia sp. were obtained in 24 h using lichenase from an alkalothermophilic Thermomonospora sp. wherein the hydrolysis was 100% with commercial enzyme Accellerase (TM) 1000. The synergistic role of beta-glucosidase in lichenan hydrolysis was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora lichenase which resulted in complete hydrolysis. The hydrolysates of lichenan obtained using Accellerase or a cocktail of Thermomonospora lichenase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.45 g/g-0.48 g/g with theoretical conversion efficiencies of 93%-96%. The Ca-alginate immobilized yeast cells were reused eight times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrolysis; Lichenan; Lichenase; Synergism; Thermotolerant yeast

Approach towards biocatalytic valorisation of barley beta-glucan for bioethanol production using 1,3-1,4 beta-glucanase and thermotolerant yeast - Divate, Rupesh; Menon, Vishnu; Rao, Mala (International Biodeterioration & Biodegradation, 2013)
The exploitation of renewable resource containing polymers other than cellulose and hemicellulose are critically important for the feasibility of biofuel production. The potential of 1,3-1,4 glucan 4-gluconohydrolyase mediated saccharification of barley beta-glucan (BG) was investigated for ethanol production using thermotolerant Saccharomyces sp. A maximum hydrolysis of 71% was obtained in 24 h using in-house produced 1,3-1,4 beta-glucanase from an alkalothermophilic Thermomonospora sp. whereas the hydrolysis was 100% with Accellerase (TM) 1000. The synergistic effect of beta-glucosidase and 1,3-1,4 beta-glucanase was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora 1,3-1,4 beta-glucanase which resulted in complete hydrolysis of BG. The hydrolysates of BG obtained using Accellerase or a cocktail of Thermomonospora 1,3-1,4 beta-glucanase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.44 g g(-1) and 0.46 g g(-1) respectively and when fermented with immobilized cells produced a yield of 0.49 g g(-1). The Ca-alginate immobilized yeast cells were reused nine times at 40 degrees C with 100% fermentation efficiency. The economics of barley-to-fuel ethanol program will ameliorate if in addition to barley starch, beta-glucan is also utilized. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-1; 4 Glucan 4-gluconohydrolyase; Barley beta-glucan; Ethanol; Hydrolysis; Synergism; Thermotolerant yeast